Correction to: A kinetic study for the Fenton and photo-Fenton paracetamol degradation in an annular photoreactor (Environmental Science and Pollution Research, (2019), 26, 5, (4312-4323), 10.1007/s11356-018-3098-4) - Audino, Francesca (2021)
A Correction to this paper has been published: https://doi.org/10.1007/s11356-021-15050-7.